Effect of dietary saponin rich soapnut (Sapindus mukorossi) shell powder on growth performance, immunity, serum biochemistry and gut health of broiler chickens. Issue 6 (4th September 2019) - Bera, Indrajit; Tyagi, Praveen K.; Mir, Nasir Akbar; Begum, Jubeda; Dev, Kapil; Tyagi, Pramod K.; Biswas, Avishek; Sharma, Divya; Mandal, Asit Baran
Abstract: This study was conducted to evaluate the effects of dietary soapnut ( Sapindus mukorossi ) shell powder (SSP), a cheap source of saponins, on growth performance, immunity, serum biochemistry and gut health of broiler chickens. The experimental design was 4×2, employing four saponin levels (0, 100, 150 and 200 mg/kg diet), each provided for two time durations (0–42 day and 21–42 day) resulting into eight dietary treatments. Results revealed no significant effect of dietary saponins on body weight gain, feed intake and feed conversion ratio of birds. The abdominal fat percentage, heterophil to lymphocyte ratio, serum cholesterol and triglyceride levels, faecal total plate count, coliform count and E. coli count decreased ( p  < .05) progressively with increasing saponin levels and lower values were observed at 150 mg and 200 mg saponin levels. Significant improvement of cell‐mediated and humoral immune response was observed in birds fed 150 mg and 200 mg saponin compared to control. The serum glucose concentration was significantly ( p  < .05) higher in control group compared to other groups. No significant effects of dietary saponin were observed on carcass characteristics, faecal Lactobacillus count, intestinal histomorphometry and cost economics of broiler chicken production. Thus, dietary saponins at 150 mg/kg diet as SSP for three weeks (21–42 days) was optimum for better immunity and welfare of birds without adverse effects on the growth performance.